(untitled) (African Journal of Law and Politics, 2025)
The duty of secrecy is imperative in banking business because it instils trust and confidence in the customers and also preserve the right to privacy. However, persevering the confidentiality of banking information at all cost may be detrimental at times. That is why the legislator has tried to reconcile the duty of secrecy and the need to disclose confidential banking information. The article set out to examine the reform of the law on banking secrecy in Cameroon with the objective of bringing out succinctly the scope of application of the duty of confidentiality. Through the doctrinal approach, the article demonstrates that the 2022 Law on Banking Secrecy has broaden the scope of the duty of confidentiality with respect to acts, deeds and information to be kept secret and to persons duty bound. It is also flexible as concerns disclosure of confidential information. Nevertheless, while saluting the reforms, the article recommends that for the proper implementation of the law, the legislator should equally enact a law on data privacy in Cameroon.